Gastronomic tourism branding influencing tourist revisit attention: a case study of Penang - Zulkipli, Nusratina; Md Sawari, Siti Salwa (2019)
Gastronomic tourism received attention recently in global. Many unique cuisine has been evolved from year to year. Some people will go to the places just to taste the cuisines and will repeated again in the future. Food plays an important role in creating tourist destination places and it is recognized as the great potential of tourism products and attractions. In that case, local food is in need of protection and preservation. However, the factor that push them to go for gastronomic tourism has rarely being discovered and most of the research paper studied about tourist satisfaction is the indicator for tourist revisit intention. Thus, this study aims to investigate the most important factor of branding as the indicator of tourist revisit intention to Penang in gastronomic tourism. This study is quantitative in nature. A total of 31 respondents that has been to Penang participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 through several analyses such as descriptive analysis, frequency analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. The outcomes of this study shows the food variety and quality has become the catalyst for tourist revisit intention to Penang. Hence, this study has significant contribution to the policy and management at Penang in order to promote their authentic cuisine as one of gastronomic tourism place in Malaysia.